Analisis Dana Pihak Ketiga Simpanan Berjangka Pada Bank Perkreditan Rakyat Di Kalimantan Timur Setelah Adanya Penjaminan Dana Simpanan Oleh Bank Indonesia - Djiu, Agustinus (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2017)
The Research analysis of public savings on Rural Banks Bank Perkreditan Rakyat in East Kalimantan Region After The Guaranted Gevernment by The Bank Indonesia, to find out the effect of fundamental factors bank as measured using the CAMEL (Capital,Asset Quality, Management, Earning and Liquidity) ratio to changes the amount of deposits and interest rates in Bank Perkreditan Rakyat Kalimantan Timur Region. CAMEL (Capital,Asset Quality, Management, Earning and Liquidity) ratios consists of capital as measured by Capital Adequacy Ratio(CAR), asset quality as measured by Non Performing Loan(NPL), management quality as measured by Non-interest Expenditures to Total Assets (NIETA), earnings as measured by Return on Assets(ROA), liquidity as measured by Cash to Assets(CTA). Research conducted in Kalimantan Timur Region is also used to find out if there are differences in the behavior of market discipline at the time of a full guarantee, IDR100 million guarantee, and IDR 2 billion guarantee. The results showed while guaranteeing full there was no fundamental factors influential to changes in bank deposits and interest rates, The Nominal Deposit Guarantee by Bank Indonesia and CAMEL (Capital,Asset Quality, Management, Earning and Liquidity) condition have an impact on the movement of public savings while the granting of IDR.100 million CAR(Capital Adequacy Ratio) and CTA (Cash to Assets) have significant positive effect to changes deposits and significant negatife to interest rates, and than NIETA (Non-interest Expenditures to Total Assets) , has significant negative to changes deposits and significant positive to interest rates, IDR 2 billion guarantee CAR(Capital Adequacy Ratio) and ROA (Return On Assets) have positive effect to changes in deposits and significant negative to interest rates. Market discipline occurs at the time of the granting of IDR.2 billion and is increasing at the moment of granting decrase to IDR.100 million , indicated by number of variables that has a significant effect to changes in deposit and interest rate. whereas when full guarantee market discipline does not occur.Keywords:Deposit guarantee, Interest rate, CAMEL (Capital,Asset Quality, Management, Earning and Liquidity), Deposits